CONGRATULATION STRATEGIES OF JORDANIAN EFL POSTGRADUATE STUDENTS - Al-Shboul, Yasser; Huwari, Ibrahim Fathi (Indonesian Journal of Applied Linguistics, 2016)
This study investigates congratulation strategies used by Jordanian EFL postgraduate students. It also investigates the types of positive politeness strategies in the congratulation speech act. Data were collected using an adopted version of discourse completion test (DCT) by Dastjerdi and Nasri (2013). Data were encoded and analyzed based on the taxonomy of congratulation strategy proposed by Elwood (2004). Furthermore, data were analyzed based on a modified version of positive politeness strategies proposed by Brown and Levinson (1987). Findings revealed that the most frequently used strategies of congratulation were illocutionary force indicating devise (IFID), offer of good wishes, and expression of happiness. Regarding the positive politeness strategies, findings revealed that the most frequently used strategies by the participants were giving gift to listener, exaggeration, and ingroup identity marker. The study concludes with a discussion of important directions for future research such as including more participants with different social background. The results are expected to be useful information in cross-cultural comparison studies and other related areas.